Autologous transplantation of mononuclear bone marrow cells in patients with acute myocardial infarction: the effect of the dose of transplanted cells on myocardial function - Meluzín, Jaroslav; Mayer, Jirí; Groch, Ladislav; Janousek, Stanislav; Hornácek, Ivan; Hlinomaz, Ota; Kala, Petr; Panovský, Roman; Prásek, Jirí; Kamínek, Milan; Stanícek, Jaroslav; Klabusay, Martin; et al. (American heart journal, 2006)
BACKGROUND: Despite the reports on successful treatment of acute myocardial infarction using autologous mononuclear bone marrow cell transplantation, many unresolved questions still remain. We studied the impact of the dose of transplanted cells on myocardial function and perfusion. METHODS: Sixty-six patients with a first acute myocardial infarction were randomized into 3 groups. Two groups were intracoronarily given mononuclear bone marrow cells in either higher (10(8) cells, higher cell dose [HD] group, n = 22) or lower (10(7) cells, lower cell dose [LD] group, n = 22) doses. Twenty-two patients without cell transplantation served as a control (C) group. RESULTS: At 3 months of follow-up, the baseline peak systolic velocities of longitudinal contraction of the infarcted wall of 5.2, 4.5, and 4.3 cm/s in C, LD, and HD groups increased by 0.0, 0.5 (P < .05 vs C group), and 0.9 cm/s (P < .05 vs LD group, P < .01 vs C group), respectively, as demonstrated by Doppler tissue imaging. Baseline left ventricular ejection fractions of 42%, 42%, and 41% in C, LD, and HD groups increased by 2%, 3%, and by 5% (P < .05 vs group C), respectively, as assessed by the gated technetium Tc 99m sestamibi single photon emission computed tomography. CONCLUSIONS: Mononuclear bone marrow cell transplantation improves regional myocardial function of the infarcted wall in a dose-dependent manner.
Keywords: srdce; Humans; lidé středního věku; myokard; Middle Aged; Myocardial Contraction; mužské pohlaví; transplantace kostní dřeně; Heart; Bone Marrow Transplantation; Myocardial Infarction; autologní transplantace; ženské pohlaví; infarkt myokardu; lidé; Myocardium; Male; Transplantation, Autologous; kontrakce myokardu; Female